Seasonal variations and comparative nutritional composition of hatchery-reared, hatchery-released, and wild black rockfish (Sebastes schlegelii) - Liu Wang; Liu Wang; Yunhai He; Xu Wei; Xinyan Liang; Xinyan Liang; Ruonan Zhang; Ruonan Zhang; Qi Liu; Qi Liu; Chenqi Wang; Chenqi Wang; et al. (Frontiers in Marine Science)
The black rockfish (Sebastes schlegelii) is a commercially important marine species in the Northwest Pacific Ocean. Its population has significantly declined due to overfishing and environmental changes. Stock enhancement has been launched in response to wild populations decline. However, limited evidence is available to confirm the ecological effects after release. Empirically, if the hatchery-released individuals are well-adapted to the wild environment, they should show good or similar nutritional conditions as well as their wild counterparts. Therefore, nutritional analysis was essential and conducted in the present study, by using 146 S. schlegelii individuals in order to compare the differences among hatchery-reared (before-release), hatchery-released, and wild conspecifics (post-release) groups in consideration of different environments during a whole stock enhancement practice. Our results exhibited that hatchery-reared S. schlegelii exhibited significantly lower levels of crude protein and amino acid content than that of hatchery-released and wild ones (P < 0.05). Specifically, both the hatchery-released and wild S. schlegelii generally showed similar trends of nutrition profiling compared with their hatchery-reared counterparts, such as moisture, crude ash, crude lipid, crude protein, and amino acid profiles (P > 0.05), indicating homogeneity in their nutritional contents. Our research suggested that S. schlegelii exhibited extensive ecological plasticity, and the variations in nutrition of a population was mainly influenced by environmental factors rather than the origin. However, several differences in fatty acid composition between hatchery-released and wild S. schlegelii indicated that hatchery-released fish might not have fully adapt to the food supply in the wild. This study provided insights into promoting responsible stock enhancement of this species in the future.